Some Notes on Monopoly Price - Coase, R. H. (Review of Economic Studies, 1937)
Journal Article Some Notes on Monopoly Price Get access R. H. Coase R. H. Coase London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 5, Issue 1, October 1937, Pages 17–31, https://doi.org/10.2307/2967577 Published: 01 October 1937